Successful management of tubular colonic duplication using a laparoscopic approach: A case report and review of the literature - Li, Gan-Bin (World J Clin Cases, 2020)
BACKGROUND: Alimentary duplication is a rare congenital disease with a reported incidence of 1 per 4500 persons, although the exact incidence has been difficult to ascertain. According to previous reports, the most common site of duplication is the ileum, and colonic duplication is rare. Due to different types and locations of the duplication, the manifestations are varied, which makes establishing an accurate diagnosis before surgery a challenge. CASE SUMMARY: A 17-year-old female patient sought evaluation in our department with constipation and chronic abdominal pain for 12 years; she had difficulty defecating and had dry stools since she was a child. An abdominal computed tomography revealed two extremely enlarged loops of bowel full of stool-like intestinal contents in the left lower abdomen, which led us to consider the possibility of colonic duplication. A laparoscopic exploration was performed, which revealed a tubular duplicated colon that shared a common opening with the transverse colon. A left hemi-colectomy was performed with a side-to-side anastomosis. The pathologic results confirmed the diagnosis. At the 6-mo follow-up, the patient was doing well without constipation or abdominal pain. CONCLUSION: Colonic duplication is a rare alimentary abnormality in adults. Due to the non-specific manifestations and low incidence, it is usually difficult to make an accurate diagnosis pre-operatively. Surgery is the mainstay of treatment, even though some patients are asymptomatic.